p-Phenyleneethynylene unit-conjugated dimeric zinc-phthalocyanines in bulk heterojunction solar cells: a comparative experimental and theoretical study - Tunc, Guelenay; Celik, Gizem Guemuesgoez; Canimkurbey, Betuel; Dedeoglu, Burcu; Gurek, Ayse Guel (Royal Soc Chemistry, 2025)
Nowadays, the photosensitivity of certain molecules, particularly phthalocyanines (Pcs), is well-studied. This field has made much progress, and several practical applications exist for these molecules. In this study, p-phenyleneethynylene-bridged two ZnPc dimers containing either bulky tert-butyl (GT57) or tert-butyl thiol (GT60) substituents at the peripheral position were synthesized as a novel donor component for bulk heterojunction (BHJ) solar cell applications. The molecular structure and photophysical properties of dimeric ZnPc derivatives were investigated by combined experimental and theoretical studies. The density functional theory (DFT) method was employed with B3LYP functional and the def2-SVP basis set to examine the designed complexes and calculate geometrical parameters and natural transition orbitals (NTOs). Additionally, the time-dependent density functional theory (TD-DFT) method was employed to investigate the optical properties through the analysis of UV-vis spectra. Dimeric ZnPc derivatives were blended as donor components alongside PCBM as the acceptor material in BHJ solar cells, achieving a maximum power conversion efficiency of 4.05%, for GT60 and compared to GT57, cells based on GT57 exhibited lower photovoltaic performance. These findings are encouraging and highlight the potential for further research on BHJ solar cells employing near-infrared-absorbing, non-aggregated dimeric ZnPc derivatives containing S heteroatoms.
Keywords: Solvent; Electrochemistry; Approximation; Porphyrins; Complexes; Trimers; Solutes; Atom